Investigation of the effectiveness of physical examination and radiologıcal imaging methods in the diagnosis of nasal bone fractures (Annals of Medical Research, 2021)
Aim: Our objective is comparing the physical examination and radiological imaging (lateral nasal x-ray and computed tomography (CT)) methods for diagnosis in patients admitted to the emergency department due to nasal trauma and referring them to the department of otolaryngology.Material and Methods: We retrospectively analyzed the physical examination and radiological imaging (lateral nasal radiography, paranasal CT) of 64 patients who were admitted to our hospital emergency department between October 2016 and October 2018 due to isolated nasal trauma and consulted to the department of otolaryngology and head and neck surgery.Results: Of the 64 patients who participated in the study, 51 were male and 13 were female. While nasal fracture was detected in 56 patients, nasal fracture was not observed in 8 patients. As a result of our study, the rate of detecting nasal fracture only by physical examination was 41%, 73.2% by lateral nasal radiography, and 85.7% by physical examination and lateral nasal radiography. With paranasal CT, nasal fracture was diagnosed in all patients. Paranasal CT was found to be statistically significantly more successful in detecting nasal fracture compared to physical examination and direct nasal radiograph findings (p = 0.002).Conclusion: As a result; physical examination and lateral nasal radiography provide useful information for diagnosis, but paranasal CT was the best diagnostic method in the diagnosis of nasal fracture.
Keywords: Lateral radiography; nasal fracture; paranasal computed tomography